Maritime Piracy and Limitations of the International Law of the Sea - Michał Wallner (Historia i Polityka, 2019)
The primary aim of this paper is to analyse the legal definition of piracy stipulated in Article 101 of the United Nations Convention on the Law of the Sea. As the title of the paper itself suggests, the phenomenon of maritime piracy is examined only from the perspective of international law of the sea, which means that state municipal laws remain beyond the scope of the analysis. The authors attempt to interpret and critically assess relevant legal provisions, rather than recount in detail facts related to cases of maritime piracy or present statistics describing the scale of this phenomenon. The article is divided into six relatively short sections. Key considerations are contained within sections 3–5, which cover the relevant provisions of the Montego Bay Convention. These sections deal, respectively, with the definition of piracy, the “private ends” requirement, and the “two-vessel” requirement. The remainder of the article is divided into introduction, historical background and conclusions.